Self‐harm in an older adult population during the COVID‐19 pandemic. Issue 2 (9th May 2022) - Obidoa, Michael; Bello, Rakiya; Hardman, Stephen
Abstract : The COVID‐19 pandemic has presented major challenges for all demographics of society. The strict lockdown measures utilised to control the spread of the virus have the potential unintended consequences of exacerbating social isolation and loneliness, which are recognised to be pre‐existing issues in the elderly population. Because of this, the pandemic may have disproportionality impacted the elderly population. One way that the distress caused by the pandemic could manifest is through self‐harm and suicide. Here, the authors present a retrospective, cross‐sectional study examining self‐harm in an older adult population in the south west of England.